Enhanced Antitumor Efficacy of Macrophage-Mediated Egg Yolk Lipid-Derived Delivery System Against Breast Cancer [Corrigendum] - Lv Y (Dove Medical Press, 2021)
Lv Y, Jun Y, Tang Z, et al. Int J Nanomedicine. 2020;15:10075–10084. The authors have advised due to an error at the time of figure assembly, Figure 5C on page 10082 is incorrect. The correct Figure 5 is shown below. The authors apologize for this error and advise it does not affect the results of the paper.   Read the original article